2013
DOI: 10.1016/j.jacc.2013.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus-Associated Vascular Impairment

Abstract: It is widely accepted that diabetes mellitus (DM) impairs endothelial nitric oxide synthase activity as well as enhances the production of reactive oxygen species, thus resulting in diminished nitric oxide bioavailability and the consequent pro-atherogenetic alterations. Important biomarkers of the vasculature are related to endothelial dysfunction, to inflammatory and coagulation processes, and to oxidative stress in DM. Several therapeutic strategies might exert favorable effects on the vasculature of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(79 citation statements)
references
References 77 publications
5
73
0
1
Order By: Relevance
“…Diabetes mellitus enhances the ROS, thus resulting in diminished NO bioavailability. Increased oxidative stress in the vasculature is a major contributor of endothelial dysfunction mediated by the O 2 - production [41] and impairment of NO bioavailability in the vascular wall in diabetes mellitus [42]. In this study we found that fenofibrate decreased the O 2 - production and increased the NO level in EPCs both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…Diabetes mellitus enhances the ROS, thus resulting in diminished NO bioavailability. Increased oxidative stress in the vasculature is a major contributor of endothelial dysfunction mediated by the O 2 - production [41] and impairment of NO bioavailability in the vascular wall in diabetes mellitus [42]. In this study we found that fenofibrate decreased the O 2 - production and increased the NO level in EPCs both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…111,112 Screening of >280 biomarkers in patients with dysglycemia showed positive associations between NT-proBNP, trefoil factor 3, GDF-15, apolipoprotein B, angiopoietin-2, osteoprotegerin and α-2-macroglobulin, and adverse cardiovascular events. been positively associated with cardiovascular risk in another study that additionally demonstrated an association of osteopontin and MMP-3 with adverse cardiovascular events.…”
Section: High-risk Groups Within the General Populationmentioning
confidence: 99%
“…This issue deserves attention because early markers of diabetes mellitus-related vascular damage remain elusive. 21,22 In this study, we have reported that Set7 expression is increased in PBM from patients with T2DM and correlates with NF-kB activation, oxidative stress, and endothelial dysfunction. The analysis of Set7-driven chromatin modification unmasked H3K4m1 on NF-kB promoter in patients with T2DM but not in controls.…”
Section: Discussionmentioning
confidence: 78%